Cultural Diversity Determining the Memory of a Controversial Social Event - Elena Paspalanova (Fondazione Eni Enrico Mattei (FEEM), 2006)
A social event from the near past socio-political policy in Bulgaria State policy of changing the names of Turkish population living in Bulgaria as a major element of the state revival process aiming at exterminating the ethnic differences in Bulgaria was chosen to study the influence of cultural diversity on memories of that event. The study aims at revealing the hypothesized complex structure of indicators of cultural diversity, which determines memory of the social event. In respect to the controversial event being an object of the memory, the following indices of cultural diversity are chosen: Ethnicity (Bulgarians vs Turks), Religion (Christian Orthodox vs Muslim), Maternal language (Bulgarian vs Turkish), National identity (Bulgarian / Turkish vs European). The research focuses on the cultural characteristics of the self as an experiencer / rememberer as well, namely social orientation (individualistic vs collectivistic). A final set of control variables is the panel of socio-demographic characteristics (gender, age, educational level, and monthly income) included in order to clarify the expected multifaceted picture of the cultural diversity influencing the memory of a social event.
Keywords: 330; Controversial Event; Memory; Individualism; Collectivism; Cultural Diversity Indices